System Methodology as a Conceptual Basis of Interdisciplinary and Transdisciplinary research - S. G. Zbrishchak (Управленческие науки)
The paper is devoted to the methodological tasks of conducting transdisciplinary research of TI, that have been leading to the tasks of integrating the knowledge of various stakeholders. The methodological framework of the study includes a systematic approach, the provisions of knowledge engineering and social psychology. The methodological basis of TI is formulated, the essence of which is the identification, coordination and integration of individual and collective structures of knowledge. The requirements to the procedure of knowledge integration of different stakeholders are defined: to form an understanding of the complexity of problems, to take into account the diversity of the real world and scientific perception of problems, the link of abstract and specific knowledge of a particular situation, the use of the concept of the common good as a regulatory basis for harmonizing multiple values and norms. Conceptual models are considered as an integration tool. The theoretical and practical significance of the study lies in the rationale for the application of methods of joint conceptual modeling as a tool for integration and coordination of various types of knowledge and organization of communication processes in a stakeholders group.